Droughts in three sites of La Pampa (Argentina) (Semiárida, 2020)
Droughts are an agroclimatic adversity appellant in very changeable climates, present normally in semiarid and subhumid regions. She affects vast regions destined for the farming production in Argentina. Drought is one adversity with more difficult evaluatingh beca use of the complexity of factors involved, including the scarcity or absence of precipitation, storage capacity for water in the soil and the relationship of drought to the annual cycle of vegetation. The Palmer's model (1965), which calculates Palmer's Drought Severity Index was calculated for characterize droughts in three sites located in the agricultural zone of La Pampa Province: General Pico, Santa Rosa y Guatraché for the period 1921-2009. During the period of analysis, the frequency of dry episodes was greater than the frequency of humid or normal periods in the three sites. General Pico had the lowest frequency of drought, followed by Santa Rosa and then Guatraché. Three sites had greater frequencies of weak droughts. Based on an analysis of the temporal distribution of dry and humid periods, a predominance of negative (dry) months was observed until the mid-1970·s. After this decade, the positive (humid) Indices increased in frequency and intensity, and negative Indices were less frequent and only they have greater magnitudes al the end of the period analyzed especially in Santa Rosa and Guatraché.
Keywords: drought; humid episodes; dry episodes; Palmer's Drought Severity Index